The effect of transformational leadership on employee performance with job satisfaction and organizational citizenship behavior as a mediation variable - Lestariasih. T, L. P. Tetty; Dewi, I Gusti Ayu Manuati (International research journal of management, IT and social sciences, 2021)
This study aims to analyze the effect of transformational leadership, job satisfaction, and organizational citizenship behavior on employee performance at the Regional Revenue Agency Office of Bali Province. The number of samples used as many as 237 respondents whose number was determined using the Slovin formula. The method of collecting data is by using interviews and questionnaires using a Likert Scale. The questionnaires as data collection method are distributed by using Google Form. The data analysis was carried out using Structural Equation Modeling-Partial Least Square (SEM PLS). The results of this study indicate that transformational leadership has a positive and significant effect on employee performance, job satisfaction has no effect on employee performance, organizational citizenship behavior has a positive and significant effect on employee performance, transformational leadership has a positive and significant effect on job satisfaction, transformational leadership has a positive and significant effect on organizational citizenship behavior, the effect of transformational leadership on employee performance is not mediated by job satisfaction, and transformational leadership has a positive and significant effect on employee performance partially mediated by organizational citizenship behavior variables.